ANALISIS STRES KERJA MEMPENGARUHI KINERJA KARYAWAN PADA KANTOR AKUNTAN PUBLIK BIMA ADI VIRGANA PAMULANG TANGERANG SELATAN - Rofiqoh, Nurul; Sularmi, Lili (Journal of Research and Publication Innovation, 2024)
Work stress is an internal condition due to physical (body) demands, the environment and social situations that have the potential to be damaging and uncontrollable. This situation can hinder daily activities, including when working. Factors that cause work stress are difficult and excessive workloads, pressure and attitudes of leaders who are less than fair and reasonable, inadequate work time and equipment, conflicts between individuals and leaders or work groups, remuneration that is too low, problems in the family such as children, wife, in-laws and others. This comprehensive final assignment aims to determine the problem of Job Stress that Affects Employee Performance at the Bima Adi Virgana Public Accounting Firm. This research uses a qualitative descriptive method, namely studying existing problems and applicable procedures. This qualitative descriptive research aims to describe what is currently happening, it includes recording, analyzing and interpreting conditions that are currently occurring or existing. In this research, data collection techniques were also carried out through interviews with employees of the Bima Adi Virgana Public Accounting Office. From the results of the interviews, it was found that there was work stress at the Bima Adi Virgana Public Accounting Firm, and it was found that the problem of work stress was not only from excessive work problems, but could be due to economic problems, problems between employees and family problems which were always linked to work problems.